Analisis Pemahaman Calon Guru Matematika terhadap Konsep Garis dan Sudut - Udiyono Udiyono; Muhammad Ridlo Yuwono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This study aims to determine the level of understanding of prospective mathematics teachers on line and angle material and their causes. This research is a case study. Subjects were selected using purposive sampling technique. This research instrument is an understanding test and interview guidelines. Method triangulation techniques are used to compare the results of understanding tests with interviews. Data analysis for understanding test results using a percentage level of understanding formula. Data analysis for interview results is data reduction, data presentation and conclusion drawing. The results showed that the level of achievement of the six aspects of understanding was less than 30%. The conclusions of this study are the level of understanding of prospective mathematics teachers in the material line and angle is still low.